Microbial Competition of Rhodotorula mucilaginosa UANL-001L and E. coli increase biosynthesis of Non-Toxic Exopolysaccharide with Applications as a Wide-Spectrum Antimicrobial - Vázquez Rodríguez, Augusto; Vasto Anzaldo, Ximena G.; Barboza Pérez, Daniel; Vázquez Garza, Eduardo; Chapoy Villanueva, Héctor; García Rivas, Gerardo; Garza Cervantes, Javier Alberto; Gómez Lugo, Jessica Judith; Gomez Loredo, Alma Elizabeth; Garza González, María Teresa; Zárate Kalfópulos, Xristo; Morones Ramírez, José Rubén (2018)
Within the last fve decades there has been an increased frequency in the emergence of bacterial strains resistant to commercially available antibiotics. Terefore, there is an urgent need to seek, develop and design new antimicrobials to treat infections and to combat bacterial strains in industrial settings. Bacteria have the ability to colonize biotic and abiotic environments through the formation of bioflms. It has been estimated that 80% of bacterial infections in humans are caused by bacterial bioflms, and 50% of the nosocomial infections are.